Effects of Soil Texture on Characteristics of Hydrograph Unit and Modelling Flood Prediction (Case Study in Separi Watershed, Kutai Kartanegara, East Kalimantan) - M. LUTHFUL HAKIM; O. HARIDJAJA; . SUDARSONO; G. IRIANTO (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2007)
A Research on effects of soil texture on hydrograph unit characteristic and flood prediction modelling in East Kalimantan need to be developed, because intensity and area of flood progressively increased. The objectives of this research are : 1) to study the effects of soil texture on the characteristic of hydrograph unit, 2) to develop flood prediction models (peak discharge and time to peak discharge) of Separi watershed, and 3) to determine an optimal landuse area composition in line with flood and Separi watershed management. The location of research site is on Separi watershed in Kutai Kartanegara, East Kalimantan at 00003’-00038’ S and 117008’-117031’ E coordinate position. Field research has been conducted from January to June 2006. The methodology of the research based on several steps, e.i. : 1) data collecting, 2) flood prediction models development, 3) model accuration testing, and 4) model application. Themodel of flood prediction based on: 1) modelling of production function and 2) modelling of transfer function. The result showed that soil texture has an effect towards peak discharge and time to peak discharge. Soil with loam texture has peak discharge higher than soil with sand and clay texture, whereas time to peak discharge of soil with clay texture is higher than soil with loam and sand texture. Flood prediction (peak discharge and time to peak discharge) based on land characteristics and watershedgeomorphology was able to simulate peak discharge and time to peak discharge, which has no different result compared with result from measurement. Analysis of optimum composition landuse with decreasing peak discharge and time to peak discharge indicated that compositions of landuse in Separi watershed are 54% for forest area, 1,9% for farm/garden, 0,12% for urban, 0,5% for paddy field, 42% for shrubs/underbrush, and 1,99% for coal-mining.